A Novel Bionic Catalyst-Mediated Drug Delivery System for Enhanced Sonodynamic Therapy - Yang, Yiling; Hua, Shaohua; Suo, Weilong; Wang, Wenbin; Wang, Longhao; Chen, Zhengguang; Liu, Kefeng; Zhao, Jie (Frontiers in Bioengineering and Biotechnology, 2021)
Ultrasound (US)-triggered sonodynamic therapy (SDT) proves itself to be a formidable tool in the fight against cancer, due to its large spectrum of uses as a non-invasive therapeutic measure, while also demonstrating itself to be a certain improvement upon traditional SDT therapeutics. However, tumour hypoxia remains to be a major challenge for oxygen-dependent SDT. This study describes the development of an innovative, multi-use, catalyst-based and improved SDT targeting cancer, through the employment of a sonosensitizing curcumin (Cur) load embedded within a MnO2 core, together with an extraneous tumor cell membrane component. The latter allows for efficient tumour recognition proprties.Hollowed-out MnO2 allows for efficient drug delivery, together with catalyzing oxygen generation from hydrogen peroxide present in tumour tissue, leading to enhanced SDT efficacy through the induction of a reduced hypoxic state within the tumor. In addition, Cur acts as a cytotoxic agent in its own right. The results deriving from in vivo studies revealed that such a biomimetic approach for drug-delivery actually led to to a reduced hypoxic state within tumor tissue and a raised tumor-inhibitory effect within mouse models. Such a therapeutic measure attained a synergic SDT-based tumor sensitization treatment option, together with the potential use of such catalysis-based therapeutic formulations in other medical conditions having hypoxic states.